2014
DOI: 10.7150/ijms.6962
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Gene Polymorphisms Associate with Microbiogical Agents in Periodontal Disease: Our Experience

Abstract: Periodontics has evolved from a simplistic model to a more complex interplay between infection and host response. Genetic factors have been a new addition to the list of risk factors for periodontal diseases. The processes leading to destruction and regeneration of the destroyed tissues are of great interest to both researchers and clinicians.The selective susceptibility of subjects for periodontitis has remained an enigma and wide varieties of risk factors have been implicated for the manifestation and progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 35 publications
1
51
0
Order By: Relevance
“…Complete examinations of soft and hard oral tissues were performed on all patients. Exclusion criteria from the study were: diseases of the oral hard or soft tissues, except caries and periodontal disease; presence/use of orthodontic appliances; need of pre-medication for dental treatment; use of antibiotics for the preceding six-month period; pregnancy or lactation; inability or unwillingness to sign informed consent; history of diabetes; HIV positive; immunosuppressive chemotherapy; and history of any disease known to severely compromise immune function [18].…”
Section: Subject Enrollment and Inclusion/exclusion Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Complete examinations of soft and hard oral tissues were performed on all patients. Exclusion criteria from the study were: diseases of the oral hard or soft tissues, except caries and periodontal disease; presence/use of orthodontic appliances; need of pre-medication for dental treatment; use of antibiotics for the preceding six-month period; pregnancy or lactation; inability or unwillingness to sign informed consent; history of diabetes; HIV positive; immunosuppressive chemotherapy; and history of any disease known to severely compromise immune function [18].…”
Section: Subject Enrollment and Inclusion/exclusion Criteriamentioning
confidence: 99%
“…All data from clinical and radiographic evaluation were collected into a dedicated periodontal folder. The periodontal probe (PCP15 -HuFriedy, Chicago, IL, USA) was inserted parallel to the vertical axis of the tooth and "walked" circumferentially clockwise around each surface of the tooth, to detect the area of deepest penetration (inclusion criteria: bleeding on probing and probing depth exceeding 3 mm) [18]. Our study recruited only Italian Caucasian subjects, and none of them had a history of diabetes mellitus or current manifestation of systemic diseases, which correlates with destructive periodontal disease.…”
Section: Subject Enrollment and Inclusion/exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…After application of the inclusion criteria, six (Ferreira Jr. et al, 2008;Karasneh et al, 2011;Shibani et al, 2011;Al-hebshi et al, 2012;Masamatti et al, 2012;Cantore et al, 2014) were included in the meta-analysis, with 726 being excluded. A flow chart illustrating the study selection process is shown in Figure 1.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Composite genotype was pointed by some authors as a susceptible for the periodontal disease and for that reason it is included in such a test who would have a goal to detect genetic susceptibility of a person to the periodontal disease and to allow its early detection which is important for right time and suitable therapy that will be able to prevent tooth loss [37,38].…”
Section: Discussionmentioning
confidence: 99%